2016
DOI: 10.1002/app5.144
|View full text |Cite
|
Sign up to set email alerts
|

Multilateralism and Regionalism in the South Pacific: World Trade Organization and Regional Fora as Complementary Institutions for Trade Facilitation

Abstract: As World Trade Organization (WTO) membership becomes almost universal, the Pacific island countries stand out as the largest group of outsiders. As the islands seek to replace reliance on preferential trading arrangements by competitive exports, market access and trade facilitation have become key policy concerns. In this context, WTO membership and regional or bilateral trade agreements are complementary institutions for increasing the potential success of new exports. The WTO sets out agreed principles for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…However, the increasing financial pressures and rising unemployment rates forced Pacific Islands people to find alternative income‐earning options. The data showed that participants adapted to adverse impacts by revitalizing their traditional socioeconomies which, prior to tourism and labour migration, used to be predominantly dependent on agriculture, fisheries, and informal sectors (Overton et al, 2018; Pomfret, 2016). For example, respondents in Tonga discussed how the disruption in global trade and limited access to seasonal workers schemes catalysed the revival of the local agriculture sector, strengthened the local labour force, and decreased their dependence on imported goods by increasing the production of import substitutes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increasing financial pressures and rising unemployment rates forced Pacific Islands people to find alternative income‐earning options. The data showed that participants adapted to adverse impacts by revitalizing their traditional socioeconomies which, prior to tourism and labour migration, used to be predominantly dependent on agriculture, fisheries, and informal sectors (Overton et al, 2018; Pomfret, 2016). For example, respondents in Tonga discussed how the disruption in global trade and limited access to seasonal workers schemes catalysed the revival of the local agriculture sector, strengthened the local labour force, and decreased their dependence on imported goods by increasing the production of import substitutes.…”
Section: Discussionmentioning
confidence: 99%
“…Pacific Island governments envisage both political and economic benefits from regional integration, including strengthening domestic commitment across the region to liberalization, attracting development, providing a single voice in international fora, enlarging the market size, and providing a gradual adjustment towards more significant (extra-regional) liberalization [ 26 ]. Intraregional trade agreements have also played an important role in trade facilitation in the Pacific [ 33 ] and facilitated sectoral cooperation and regional service delivery [ 34 ]. The overall impact of intra-regional agreements on trade, however, has been limited.…”
Section: Introductionmentioning
confidence: 99%